Kekuatan sikap positif: Peran perilaku prososial dan dukungan sosial dalam meningkatkan kebersyukuran - Taufik Akbar Rizqi Yunanto (Jurnal Psikologi Ulayat, 2020)
Existing literature demonstrates that gratefulness is a critical determinant for individuals’ well-being and their quality of interpersonal relationships. A sense of gratefulness provides a perspective in which individuals could have a positive evaluation in life, including the way they view challenges. Positive appreciation of life’s challenges would allow individuals to increase their coping ability and would motivate them to do prosocial behavior. This study aims to determine the role of prosocial behavior and social support to individuals’ sense of gratefulness. Participants in this study consisted of 250 participants aged between 13–55 years old. The instruments used in this research were Gratitude Questionnaire, Philosophies of Human Nature Altruism Scale, and Social Support Scale. Multiple regression analysis was used to analyze the data. The result revealed a strong contribution between prosocial behavior and social support toward gratitude. Gratitude and prosocial behavior contribute in enabling individuals to have a positive evaluation oflife.